The impact of solid waste recycling on environmental security of countries according to the Environmental Performance Index (EPI) 2022: A study of leading international models - Hicham, Benazza; Soumeia, Derbal; Fatima, Sayah; Mohamed, Trifa; Amine, Boumedini Mohamed (International journal of economic perspectives, 2024)
Sustainable development requires a deep understanding of the environment and the growing environmental challenges facing all countries. The Environmental Performance Index (EPI) ranks countries on a sustainability scale based on a weighted aggregate of several relevant environmental indicators. Solid waste recycling is considered one of the modern and safer methods that, if adopted, can transform solid waste into a new resource, thereby reducing the risks associated with the unsafe disposal of solid waste and ultimately achieving environmental security. This means ensuring the ability to mitigate the effects of environmental pollution from waste, which has a positive impact on air and water quality and agriculture, thereby reducing the effects of global warming and climate change, as reflected in the 2030 Sustainable Development Agenda. Numerous global environmental and academic institutions have focused on studying and evaluating countries' performance in this regard by establishing indices, including the Environmental Performance Index (EPI), published biennially by Yale University and Columbia University, which aims to strengthen the Sustainable Development Goals for the 2015-2030 Agenda. Global waste is expected to increase to 3.40 billion tonnes by 2050, more than twice the rate of population growth. Daily waste generation per capita is expected to increase by 19% in high-income countries by 2050, compared to around 40% or more in low- and middle-income countries. In addition, the total amount of waste generated in low-income countries is expected to more than triple by 2050. This study aims to demonstrate the impact of solid waste recycling on the environmental security of countries according to the EPI 2022, with a review of the experiences of some countries.